Amos Oz : the legacy of a writer in Israel and beyond - Omer-Sherman, Ranen (SUNY series in contemporary Jewish literature and culture., 2023)
"The veteran contributors to this volume take as their central drama, and their essential task for analysis, the enduring literary and political legacy of Israel Prize laureate Amos Oz (1939-2019). Born a decade prior to the establishment of the state of Israel, in what was then Palestine under British rule, Oz's life spanned the country's entire history, and both his fiction and nonfiction restlessly probe and illuminate its fraught conflicts, contradictions, and ambivalences. Throughout his career, Oz grappled frankly with the often-painful realities of Israeli life while also celebrating the ebullience of the Israeli spirit, and his sophisticated understanding of the sociopolitical turmoil of his society was always accompanied by intensely lyrical language and deep penetrations into the vulnerabilities of the human psyche. The volume's twenty contributors bring an exciting diversity of concerns and perspectives to Oz's most celebrated novels (including his powerfully resonant final novel, Judas) as well as to overlooked facets of his oeuvre, illuminating the breathtaking scope of his literary legacy. Together, they offer gripping analyses of his urgent and profoundly universal works about political and romantic dreamers whose heartfelt struggles with both their own human frailties and those of the state ultimately resonate far beyond Israel itself."--Back cover.